The Existence of the Role of Indonesia National Central Bureau (NCB-INTERPOL) in Extradition Cooperation as an Effort to Eradicate the Transnational Crime - Januari Nasya Ayu Taduri; Raden Muhammad Arvy Ilyasa; Rastini Rastini (Advances in Police Science Research Journal, 2021)
The end of this decade, transnational crime increased rapidly. Transnational crime greatly affects the defence, security, economy and social aspects of a country's society. In addition, transnational crime has caused anxiety around the world. Indonesia as a country that has a strategic geographic location and is often the target of transnational crime destinations, should make efforts to eradicate transnational crime. So far, Indonesia through NCB Interpol has made various efforts to overcome transnational crimes, such as cooperate with several other countries. This paper will discuss the role of the National Central Bureau (NCB) of Interpol Indonesia in extradition cooperation as the form of efforts to eradicate transnational crime. The purpose of this paper is to provide an overview of the systematics and roles of extradition cooperation carried out by Indonesia and the destination country. This paper uses a normative legal research method based on several governing laws and regulations. It is hoped that this paper can provide a new understanding of extradition cooperation in handling transnational crimes against readers.